A impressão 3d no ensino de química: projeto e fabricação de modelos moleculares e sua aplicação no ensino de isomeria geométrica e ótica - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This dissertation addresses innovation in Chemistry education through 3D printing, focusing on the development of three-dimensional molecular models. Identifying a gap in the availability of modular molecular models for 3D printing, this study introduces the "3DModularKit," a set of digital files for 3D printing molecular model components. These models, not only economically viable, proved to be robust and adaptable to different 3D printers, allowing the assembly of various organic molecular structures. In addition to technical development, the project includes a training course for future chemistry teachers, emphasizing the application of models in teaching isomerism. This course aims to integrate 3D printing technology into the educational context, providing future educators with innovative tools and practices for more interactive and engaging chemistry education. Through an approach that combines theory and practice, this dissertation explores the potential of 3D-printed molecular models as a pedagogical tool for teaching abstract concepts such as molecular structure and isomerism. With a focus on meaningful learning, the work highlights the importance of didactic models in chemistry education, demonstrating how 3D printing can transform science education, preparing students for the challenges of ontemporary science.
Keywords: Modelo molecular; Impressão 3D; Ensino de química; Isomeria; Molecular model; 3D printing; Chemistry education; Isomerism; CNPQ::OUTROS